Cyclohexyldiphenylphosphine in heck coupling / Nurulhidayah Abdul Kader - Abdul Kader, Nurulhidayah (2008)
This study describes mainly the significance of phosphine ligand that is cyclohexyldiphenylphosphine. Phosphine ligand have been used in Heck reaction together with other conditions chosen such as silver nitrate, potassium acetate, palladium chloride and dimethylformamide to synthesise stilbene that is 3,4-dimethoxy- 12-acetoxystilbene. All reaction conditions chosen were appropriate to synthesise the desired compound. This study was carried out using Heck reaction to achieve the objective of this study. Heck reaction was found to be the efficient method. Prior to Heck reaction, the hydroxyl group in 4-iodophenol was protected by forming 4- iodophenylacetate. The coupling of 4-iodophenylacetate with 3,4-dimethoxystyrene gave 3,4-dimethoxy-12-acetoxystilbene. The product was analyzed using TLC and extracted using ethyl acetate and hexane. Purification of the reaction product was done by using column chromatography. The chemical structure of stilbene was confirmed by nuclear magnetic resonance spectroscopy.